Studi Profesionalisme Guru Bahasa Arab dalam Meningkatkan Kemahiran Berbahasa - Iza Zainal Ambiya; Sofyan Sauri (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2024)
This study was motivated by student UMBN results in MA Majalengka Negeri, which still needs to be below the KKM; the low teacher competence fears this. This research focuses on one of four essential competencies, namely professional competence. This study aims to describe the professional competence of Arabic teachers in increasing language skills. The method used in this study is phenomenology with a descriptive qualitative approach. The results of this study show that the professional competence of Arabic teachers in Majalengka MA Negeri needs to be significantly improved, and at this time, professional competency research is considered sufficient. The focus of the main improvement is the development of professionalism through reflective actions that can improve teachers' quality of learning and professionalism. Improving professional competence is hoped that Arabic teachers can be more effective in increasing Arabic language skills.